Oneiric Reality of “The Rime of the Ancient Mariner”: A Jungian Analysis - Zahid Ali Shah, Syed; Jamal Khattak, Nasir (The Journal of Humanities & Social Sciences, 2022)
The Rime of the Ancient Mariner’s somewhat awkward reception initially put Coleridge into a difficulty of how to defend its lack of logic and unintelligibility of events. As a handy solution to the problem he sub-titled the poem as ‗a poet‘s reverie.‘ This topical strategy proved counterproductive. In the wake of psychoanalytic literary criticism this aspect of the poem is greatly focused upon to explore the unconscious workings of the mind as a backstage performance. Mostly judged on the bases of the ballad‘s dream-like atmosphere, there have been speculations on its sources of ancestry and frequent efforts have been made to justify these connections one way or the other. If placed within the atmosphere of dreams and soundly defended with arguments, the poem would serve not only to read its complicated symbolic patterns and some seemingly illogical incidents, but also establish a connection of the dream-world to our psychological dynamics as human beings. The making of connections simultaneously smoothens out disturbances in the mind by integrating new material—calming a storm—and also produces more and broader connections by weaving in new material. It does not simply consolidate memory, but interweaves and increases memory connections. In the Mariner‘s story, which is by and large an oneiric experience, his dream symbols reflect the condition of his inner world.